Healthcare for Persons with Intellectual and Developmental Disability in the Community - Ervin, David A.; Hennen, Brian; Merrick, Joav; Morad, Mohammed (Frontiers in Public Health, 2014)
Introduction While there has been impressive progress in creating and improving community healthcare delivery systems that support people with intellectual and developmental disabilities (IDD), there is much more that can and should be done. Method This paper offers a review of healthcare delivery concepts on which new models are being developed, while also establishing an historical context. We review the need for creating fully integrated models of healthcare, and at the same time offer practical considerations that range from specific healthcare delivery system components to the need to expand our approach to training healthcare providers. The models and delivery systems, and the areas of needed focus in their development are reviewed to set a starting point for more and greater work going forward. Conclusions Today, we celebrate longer lifespans of people with IDD, increased attention to the benefits of healthcare that is responsive to their needs, and the development of important healthcare delivery systems that are customized to their needs. We also know that the growing body of research on health status offers incentive to continue developing healthcare structures for people with IDD by training healthcare providers about the needs of people with IDD, by establishing systems of care that integrate acute healthcare with long term services and support, by developing IDD medicine as a specialty, and by building health promotion and wellness resources to provide people with IDD a set of preventative health supports.